Isolation, identification and characterization of Rhizobium from hyacinth bean (Lablab niger) root nodule and study its effect on plant growth and nitrogen fixation ability - Yshita, Khadiza Nasrin (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Microbiology, 2017.